O filho que late: uma compreensão do fenômeno “mãe de pet” na contemporaneidade - Kalaf, Sophia Porto (2024)
Living with dogs has increasingly become a significant aspect of people's lives, leading them to engage in services related to animal health, hygiene, and well-being, such as pet-friendly daycare centers and establishments. New family configurations, marked by the dissolution of the nuclear and traditional family, alongside women's greater participation in the workforce, have reshaped generational dynamics over the past decades. Delayed motherhood or the choice not to have children are increasingly debated among women. At the heart of the modern experience lies the urgency to conserve nature, a sense of hopelessness in humanity, and the transient nature of things. The overarching aim of this study was to comprehend the "pet mother" phenomenon, considering the interaction between the researcher and the dyad (pet owner and dog). Seven residents of São Paulo, who identified themselves as "pet mothers," along with their respective dogs, participated in the study. The encounters occurred through two main avenues: immersion in the relational environment (home) and dialogue, facilitated by meetings at participants' homes with the presence of their dogs. In line with the journey embarked upon in this study, each dyad was given a name inspired by a natural element, chosen based on its meanings, the history of the relationship, and the impression each made during the encounter. Grounded in the phenomenological-existential approach that underpins this research, meaningful units emerged from the dialogues, presented with excerpts corresponding to each unit, followed by a comprehensive synthesis: nurturing the dog; pet community; communication with the dog; care and guardianship of the dog; adaptations in the home and routine; transience and temporality; adoption, purchase, and breeds. Consistent with the research trajectory, as we venture into the unknown to explore new landscapes, the discussion serves as a moment to synthesize what was gleaned from the encounters with the dyads, informed by the theoretical context previously discussed. Entering the homes of the pet owners necessitated a phenomenological stance of openness to experience and allowing oneself to be transformed by it, ensuring the process unfolded as organically as possible. Investigating the relationship with dogs implicated us from the outset in the phenomenon of "pet motherhood." We emphasize the importance of guidelines for fostering conditions conducive to planetary well-being, as proposed by the 2030 Agenda (UN, 2015) and the 17 Sustainable Development Goals (SDGs). Contemplating the relationship between humans and dogs, particularly the phenomenon of "pet motherhood," cannot be divorced from the context in which it occurs, as viewing the phenomenon in isolation would be fragmentary. It necessitated a clinical approach that considers contemporaneity and how we have experienced relationships in general, in order to progress towards understanding the relationship. This work was financed by the Conselho Nacional de Desenvolvimento Científico e Tecnológico – Brazil (CNPq). Chamada 07/2022 - Project n. 131859, part of the institutional project: “Subjectivities and promotion of mental health: sustainable development in the contemporary psychological clinic” (Call 07/2022, CNPq, process No. 131859/2022-6), and financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001. Project n. 88887.675992/2022-00